Catalytic Activity of Cr2O3/sepiolite in the oxidation of benzyl alcohol - Thao, Nguyen Tien; Nhu, Nguyen Thi; Thuan, Ngo Thi (Vietnam Journal of Science and Technology, 2018)
Cr2O3/sepiolite samples with different loadings have been prepared through the precipitation method and characterized by several physical methods such as XRD, TEM, BET, and TGA... The as-prepared materials have large surface area, high distribution of Cr2O3 nanoxides on the nanofibrous sepiolite. The catalysts have been tested in the oxidation of benzyl alcohol with t-BuOOH. Chromium oxides were found to be active sites for the oxidation of benzyl alcohol to aldehyde. The catalytic activity varied with reaction time and temperature. The appropriate temperature is about 60-70oC with conversion of 40-60% and benzaldehyde selectivity of 90%.